Analysis of the Effect of World Crude Oil Prices, Exchange Rates, Inflation, Dow Jones Industrial Average, and the Nikkei 225 Index on the Composite Stock Price Index - M. Rizki Nasution; Rujiman Rujiman; Ahmad Albar Tanjung (PT Mattawang Mediatama Solution, 2023)
This study aimed to analyze and determine the effect of world crude oil prices of the WTI type, Exchange Rate, Inflation, Dow Jones Industrial Average Index, and Nikkei 225 Index on the Composite Stock Price Index. The data collection technique in this study uses the Correction Model (ECM) method. The results of this study indicate that the application of the error correction model (ECM) that has been used can provide an explanation of the influence of world crude oil prices, exchange rates, inflation, Dow Jones Industrial Average, and Nikkei 225 Index on the Composite Stock Price Index. Overall in the long-term model the variable world crude oil prices, exchange rates, inflation, dow jones industrial average, and nikkei 225 index has a variation of 0.784464 or 78.44% able to simultaneously or together affect the value of the composite stock price index, while the remaining 21.56% is influenced by variables outside this variable. The short-term model has a negative and significant effect on the composite stock price index, this is indicated by a probability value that is less than the 5% significance value (0.0378 <0.05). Simultaneously the variable world crude oil prices, exchange rates, inflation, dow jones industrial average, and nikkei 225 index has a variation of 0.430077 or 43% where the variation in the development of up or down can jointly affect the value of the composite stock price index, while the remaining 57% is influenced by variables outside this research variable.